Seven years of embracing the sustainable development goals: perspectives from University of South Africa’s academic staff - Nhamo, Godwell; Chapungu, Lazarus (Frontiers in Education, 2024)
As this paper was being finalised, the world was left with less than seven of the 15 years of Sustainable Development Goals (SDGs) implementation to 2030. There were still huge gaps in the attainment of the SDGs in institutions of higher learning globally, especially that COVID-19 brought a barrier leading to a known pushback. However, the pandemic did not imply there was no work done prior, during and after COVID-19. This paper investigates the extent to which the University of South Africa's academic staff activated and mainstreamed the SDGs in their core mandates between 2016 and 2022. Data was generated through a survey (n=121), participatory action research, and document analysis. It emerged there is a greater degree of awareness of the SDGs, with 78% of academic respondents confirming this. However, the percentages drop across the four core mandate areas when it comes to SDGs implementation. About 52.6% of academics indicated they were promoting SDGs in their teaching, research (63.3%), community engagement (55.5%) and academic citizenship (54.5%). Findings further reveal key enabling institutional policies like the SDGS Localisation Declaration, and the Africa-Nuanced SDGs Research Support Programme. Large gaps remain on the publication front, where over 60% of the responding academics had not published an article explicitly on SDGs. There is also bias in publications towards certain SDGs. The work recommends that UNISA management continue raising awareness on the SDGs and systematically address barriers identified in the main paper to enhance the mainstreaming of the SDGs across all core mandate areas.